Tafsir Al-Qur’an Berkemajuan: Exploring Methodological Contestation and Contextualization of Tafsir At-Tanwir by Tim Majelis Tarjih dan Tajdid PP Muhammadiyah - Indal Abror; Muhammad Nurdin Zuhdi (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2018)
This article discusses Tafsir At-Tanwir (2016), a work composed by the Majelis Tarjih dan Tajdid PP Muhammadiyah. The focus of this study is to reveal the background behind the writing of Tafsir At-Tanwir, in addition to the exploration of methods and approaches used in this work. It will also observe the extent to which the exegetical materials of this work respond to the current issues. The article is a library research with descriptive-critical-analytic method. The lens of contemporary tafsir paradigm is also used as the approach to analyse the data. From the analysis that has been carried out, this research concludes several important remarks. First, in addition to being written with the aim of utilizing the symbolic capital of the people derived from the guidance of the Qur’an in order to awaken their ethos and build a progressive Indonesian civilization, the birth of Tafsir At-Tanwir is a form of Muhammadiyah’s commitment which from the beginning stood up to al-Ruju ‘ila al-Qur’an wa al-Sunnah (Back to the Qur’an and Sunna). Second, the method used in Tafsir At-Tanwir is the tahlili (analytic)-cum-mawdu’i (thematic), while the approach used in Tafsir At-Tanwir is a combination of three approaches; Bayani, Burhani and Irfani. Third, Tafsir At-Tanwir has three special characteristics: 1) responsive interpretations. 2) interpretations that generate dynamics; and 3) Interpretations that generate ethos. In this work, there are also four ethos that are built in: the ethos of worship, economic ethos and work ethic, social ethos, and scientific ethos.[Artikel ini membahas tentang Tafsir At-Tanwir (2016) karya Tim Majelis Tarjih dan Tajdid PP Muhammadiyah. Adapun yang menjadi fokus kajian dalam artikel ini adalah mengungkap latarbelakang penulisan Tafsir At-Tanwir. Selain itu, artikel ini juga akan mengupas metode dan pendekatan yang digaunakan dalam Tafsir At-Tanwir dan sejauh mankah produk tafsir Tafsir At-Tanwir dalam merespons dan menjawab problem-problem aktual kekinian. Penelitian ini merupakan jenis penlitian pustaka. Metode yang digunakan dalam deskriptif-analisis-kritis dengan menggunakan pendekatan paradigma tafsir kontemporer. Dari analisis yang telah dilakukan penelitian ini mnyimpulkan bahwa: pertama, selain ditulis dengan tujuan untuk memanfaatkan modal simbolis umat yang dapat digali dari tuntunan kitab suci al-Qur’an dalam rangka membangkitkan etos umat dan membangun peradaban Indonesia yang berkemajuan, lahirnya Tafsir At-Tanwir merupakan bentuk komitmen Muhammadiyah yang sejak awal berdiri menggelorakan al-Ruju’ ila al-Qur’an wa al-Sunnah. Kedua, metode yang penafsiran yang digunakan Tafsir At-Tanwir adalah metode tahlili cum tematik. Sedangkan pendekatan yang digunakan dalam Tafsir At-Tanwir adalah gabungan tiga pendekatan Bayani, Burhani dan Irfani. Ketiga, Tafsir At-Tanwir memiliki tigakarakteristik: 1) Tafsir Responsivitas. 2) Tafsir yang Membangkitkan Dinamika; dan 3) Tafsir yang Membangkitkan Etos. Dalam Tafsir At-Tanwir ada empat etos yang dibangun, yaitu: etos ibadah, etos ekonomi dan etos kerja, etos sosial, dan etos keilmuan.]